Crafting Design Strategy on Seaweed Industry in Indonesia - Muhammad Gunawan Sani Saputro; Nunung Nuryartono; Bustanul Arifin; Nimmi Zulbainarni (School of Business, Bogor Agricultural University (SB-IPB), 2021)
The global demand for seaweed is expected to increase in the coming years due to new product development using seaweed. There are many benefits of seaweed such as pharmaceuticals, cosmetics, food industries, textiles, paper, and bioenergy production. On the other hand, Indonesia, as the archipelago country with the second-longest coastline after Canada, is expected to achieve competitiveness so Indonesia benefit more from the seaweed industry. This study aims to get the landscape of the seaweed industry and to select strategies. The strategies are designed using the Structural Equation Modelling Method – Partial Least Square (SEM – PLS). The findings of this study are the competitive advantage of Indonesia's carrageenan-producing seaweed industry using descriptive statistical methods through the perception model show considered weak. The three main parameters of concern are assessed as low-cost leadership, ability to increase export value and self-sufficiency in meeting the needs of domestic seaweed. The analysis also shows that the influence of innovation and stakeholder support on increasing the competitive advantage of Indonesia's carrageenan-producing seaweed industry is considered significant. Innovation is represented by the latent variable attributes of innovation, communication channels and the role of change agents, which are concluded to have a significant effect both directly and indirectly on the industry's competitive advantage. Keywords: seaweed industry, competitiveness, carrageenan, innovation, SEM-PLS, stakeholder support